Helminths, polyparasitism, and the gut microbiome in the Philippines. Issue 3 (March 2020) - Gordon, Catherine A.; Krause, Lutz; McManus, Donald P.; Morrison, Mark; Weerakoon, Kosala G.; Connor, Mairead C.; Olveda, Remigio M.; Ross, Allen G.; Gobert, Geoffrey N.
Graphical abstract: Highlights: We present novel clinical data and unique findings on the microbiome of villagers from a rural area of the Philippines. This builds on cohorts of individuals with well-defined polyparasitism through DNA sequencing-based microbiome profiling. The cohorts size and complexity of helminth infections presented new host microbiome associations. The number or diversity of worm species present also increases the richness of the host microbiome. Bacterial associations with helminth infection status and complexity provided highly statistically significant findings. Abstract: Polyparasitism, involving soil-transmitted helminths. and Schistosoma blood flukes, is common in low to middle income countries. These helminths impact on the gut environment and can cause changes to the gut microbiome composition. Here we examined the gut microbiome in individuals with polyparasitism from two human cohorts in the Philippines utilising DNA sequencing-based profiling. Multiple helminth species infections were high with 70.3% of study participants harbouring at least two parasite species, and 16% harbouring at least five species. Increased numbers of helminth co-infections, in particular with the gut-resident soil-transmitted helminths, were significantly associated with increased bacterial diversity; however no significant parasite-gut microbiome associations were evident for individuals infected only with Schistosoma japonicum . In general, a healthy gut is associated with high bacterial diversity, which in these human cohorts may be the result of helminth-mediated immune modulation, or due to changes in the gut environment caused by these parasitic helminths.